Clinical-pathological features and molecular background of oligodendrogliomas - G. Popescu; Francesca Paslaru; A.C. Paslaru; M. Apostol; M.C. Zaharia; M. Popescu; R.M. Gorgan (Romanian Neurosurgery, 2022)
Background: Diffuse gliomas are the most frequent primary central nervous system (CNS) neoplasms, originating from the parenchyma itself, oligodendrogliomas accounting for approximately 10% of cerebral gliomas. For the past 20 years, the study of genetic/molecular mechanisms of gliomagenesis and progression has gradually come into focus. However, the biological and clinical significance of these mutations is still to be completely characterized. The purpose of this article is to describe our clinical experience with oligodendrogliomas and to review the current literature, in order to better describe the characteristics of the molecular/genetic oligodendroglioma subgroups.